Ujrah Pembaca Al-Qur’an Pada Tempat Pemakaman Desa Keude Blang Aceh Timur Perspektif Fikih Muamalat - Rasyidin Rasyidin; Asrur Rahmah (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
This article examines the ujrah of Al-Qur’an readers at the public cemetery of Keude Blang village, East Aceh, from the perspective of muamalat fiqh. The author uses the muamalat fiqh theory. From the results of research in Keude Blang Village, East Aceh, it can be concluded that the ujrah for renting a Quran reader at the Public Cemetery has been practiced since time immemorial and for ujrah itself the tariff has been set at IDR 300,000 per day for one person and in Keude Blang it has also been formed a special group of readers of the Koran as many as 6 people in one group. In fiqh muamalat, it is permissible to rent an Al-Qur’an reader, but it is necessary to understand that reading the Koran is an act of worship and not having the intention of reading the Koran is a profession to earn money and instill a sense of sincerity in the heart without expecting anything in return. From humans but does this to worship and help fellow Muslims and considers the ujrah given to the readers of the Koran in public cemeteries as alms.